2015
DOI: 10.1038/srep13861
|View full text |Cite
|
Sign up to set email alerts
|

X-ray irradiation activates K+ channels via H2O2 signaling

Abstract: Ionizing radiation is a universal tool in tumor therapy but may also cause secondary cancers or cell invasiveness. These negative side effects could be causally related to the human-intermediate-conductance Ca2+-activated-K+-channel (hIK), which is activated by X-ray irradiation and affects cell proliferation and migration. To analyze the signaling cascade downstream of ionizing radiation we use genetically encoded reporters for H2O2 (HyPer) and for the dominant redox-buffer glutathione (Grx1-roGFP2) to monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…During the last decades, multiple efforts have been made to uncover the molecular events following radiation exposure and subsequent irradiation-triggered pathways including induction of an inflammatory response ( 41 , 42 ). We have recently reported that an increase in ROS following X-irradiation with doses ≥1 Gy results in both nuclear and cytoplasmic detection in malignant cells ( 11 , 12 ). An increase in cytosolic ROS further triggers a Ca 2+ -mediated signal transduction cascade, which eventually activates Ca 2+ sensitive K + channels and causes membrane hyperpolarization ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decades, multiple efforts have been made to uncover the molecular events following radiation exposure and subsequent irradiation-triggered pathways including induction of an inflammatory response ( 41 , 42 ). We have recently reported that an increase in ROS following X-irradiation with doses ≥1 Gy results in both nuclear and cytoplasmic detection in malignant cells ( 11 , 12 ). An increase in cytosolic ROS further triggers a Ca 2+ -mediated signal transduction cascade, which eventually activates Ca 2+ sensitive K + channels and causes membrane hyperpolarization ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that an increase in ROS following X-irradiation with doses ≥1 Gy results in both nuclear and cytoplasmic detection in malignant cells ( 11 , 12 ). An increase in cytosolic ROS further triggers a Ca 2+ -mediated signal transduction cascade, which eventually activates Ca 2+ sensitive K + channels and causes membrane hyperpolarization ( 11 , 12 ). Moreover, upon contact with antigen presenting cells, mitogens or IR, T-lymphocytes respond with a rise in [Ca 2+ ] cyt ( 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion channels in the plasma and inner mitochondrial membrane have been reported in primary tumors to contribute to the stress response and survival of irradiated tumor cells. In particular, members of the transient receptor potential family of nonselective cation channels such as TRPV6 [ 78 ] and TRPM2 [ 79 ] or K + channels including K v 3.4 [ 80 ], K Ca 3.1 (IK Ca ) [ 79 , 81 , 82 , 83 , 84 , 85 ], and BK Ca [ 86 , 87 ] are activated in the plasma membrane by ionizing radiation. Mechanistically, these radiogenic channel activities generate Ca 2+ signals which regulate downstream targets via Ca 2+ -regulated effector proteins such as CaMKII kinases that subsequently interfere with cell motility, cell cycle control or DNA repair [ 80 , 82 , 85 ].…”
Section: Radiotherapy Of Brain Metastasesmentioning
confidence: 99%
“…20,21 In addition, X-ray irradiation can also activate K + channels in A549 and HEK293 cells. 22 Inhibition of K + efflux by using Kv channel blockers or by increasing extracellular K + concentrations inhibit stress-induced activation of signaling pathways and apoptosis in many cell types including corneal epithelial cells. 2326 The Kv channel type activated by UV irradiation and hypoxic stress in corneal epithelial and other cells has been determined to be the Kv3.4 and Kv2.1 Kv channels by using electrophysiological and biochemical approaches.…”
mentioning
confidence: 99%